2015
DOI: 10.1007/s00380-015-0785-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of AST-120 on the progression and prognosis of pre-dialysis chronic kidney disease: a 5-year retrospective study

Abstract: AST-120 has been used widely in Japan to slow the deterioration of renal function in patients with chronic kidney disease (CKD) by decreasing uremic toxins. The heart and the kidney are closely related, with cardiorenal interaction being very important. This retrospective study examined whether AST-120 influences the prevalence of dialysis induction, mortality, and cardiac and stroke events in CKD patients. The study included 278 patients diagnosed with chronic renal failure (CKD stage: III-V) in 2006. Of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…One hundred twenty-eight patients received AST-120 (6 g/day), while the remaining 150 patients did not. The prevalence of dialysis induction, mortality, and cardiovascular events in patients treated with AST-120 was significantly lower after 3 and 5 years compared with the prevalence observed in the untreated patients, suggesting that long-term treatment with AST-120 may improve the prognosis of CKD patients in the predialysis stage [124,125].…”
Section: Evidence From (Pre)clinical Studiesmentioning
confidence: 88%
See 2 more Smart Citations
“…One hundred twenty-eight patients received AST-120 (6 g/day), while the remaining 150 patients did not. The prevalence of dialysis induction, mortality, and cardiovascular events in patients treated with AST-120 was significantly lower after 3 and 5 years compared with the prevalence observed in the untreated patients, suggesting that long-term treatment with AST-120 may improve the prognosis of CKD patients in the predialysis stage [124,125].…”
Section: Evidence From (Pre)clinical Studiesmentioning
confidence: 88%
“…Additional evidence can be extrapolated from studies restoring the OS imbalance of kidney disease. Indeed, some interventional studies in humans suggest improvement of renal injury or creatinine clearance with the correction of the OS imbalance [79,[124][125][126][127].…”
Section: Evidence From (Pre)clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with chronic kidney disease (CKD), elevated levels of indoxyl sulfate and p-cresyl sulfate are associated with increased risk of all-cause mortality, and p-cresyl sulfate was associated with an increased risk of cardiovascular events [12]. Administration of the oral sorbent AST-120, that prevents intestinal absorption of PBUT precursors, has been associated with a lower risk of mortality and cardiovascular events [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…After 3 and 5 years, the incidence of dialysis induction, mortality, and cardiac and stroke events in patients who underwent AST-120 treatment was meaningfully lower ( p < 0.0001) than that of the control group. The study indicated that long-term treatment with AST-120 improves the prognosis of CKD patients at the pre-dialysis stage [ 118 ].…”
Section: Clinical Trials Involving Ast-120mentioning
confidence: 99%